Building an Aprista People: The Newspaper La Tribuna in Its First Year of Existence - Bergel, Martín (2018)
This article offers a meticulous reconstruction of the La Tribuna newspaper in its first year of existence. From a perspective that addresses both its discursive and material aspects, and in dialogue with recent historiography on the press and printed culture in Latin America, this essay argues that the official newspaper of APRA played a crucial role in the popularization of the party as well as in the very construction of the notion of an «Aprista people» («pueblo aprista»).La Tribuna was a tool that organized and gave visibility to the life of the party. But its initial success was not merely due to the fact of having positioned itself in that role, but also to having effectively coupled itself with the process of the periodical press’s modernization in Peru.